1993
DOI: 10.1021/bi00091a029
|View full text |Cite
|
Sign up to set email alerts
|

Rate-equilibria relationships in intramolecular proton transfer in human carbonic anhydrase III

Abstract: Maximal turnover rates for the dehydration of HCO3- catalyzed by the zinc metalloenzyme carbonic anhydrase III are limited by a proton transfer to zinc-bound hydroxide in the active site. We have used site-directed mutagenesis to place a proton donor, histidine, at position 64 and used 18O exchange between CO2 and water measured by mass spectrometry to determine the rates of intramolecular proton transfer to the zinc-bound hydroxide. In a series of site-specific mutants, the values of pKa of the zinc-bound wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
147
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 90 publications
(157 citation statements)
references
References 41 publications
10
147
0
Order By: Relevance
“…This lack of curvature is in contrast to the very curved free energy plots for bimolecular proton transfer between nitrogen and oxygen acids and bases occurring non-enzymatically in solution (39) and is also in contrast to the very curved plots and low intrinsic kinetic barrier observed for general acid catalysis in site-specific mutants of carbonic anhydrase (40). The lack of curvature in Fig.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…This lack of curvature is in contrast to the very curved free energy plots for bimolecular proton transfer between nitrogen and oxygen acids and bases occurring non-enzymatically in solution (39) and is also in contrast to the very curved plots and low intrinsic kinetic barrier observed for general acid catalysis in site-specific mutants of carbonic anhydrase (40). The lack of curvature in Fig.…”
Section: Discussionmentioning
confidence: 66%
“…This observation was made both for non-enzymatic proton transfer between electronegative atoms (41,42) and for the enzymatic case of carbonic anhydrase (40,43). An explanation for a maximum in isotope effect near ⌬pK a value of zero in proton transfer reactions is based on a comparison of symmetric and asymmetric transition states by Westheimer (44).…”
Section: And 2) and Solvent Hydrogen Isotope Effects For Activation Omentioning
confidence: 99%
“…The exothermicity of the reaction from the present calculations, 4.4 kcal/mol with ZPE, is in reasonable agreement with experimental estimates. The reaction is thought to be nearly thermoneutral in the protein based on the similar pK a values of the zinc-bound water (estimated to be around 6 32 ) and His 64 (pK a ∼ 7 46 ).…”
Section: Resultsmentioning
confidence: 99%
“…30 The measured rate constant for the proton transfer in the wild-type CA is on the order of 10 6 s -1 (the activation free energy for proton transfer in solution is estimated to be 2.4 kcal/mol from NMR relaxation measurement, 31 which corresponds to a rate on the order of 10 s -1 ), and a substantial effort has been made to understand the correlation between the proton transfer rate and the pK a difference between the proton donor and the acceptor in the framework of Marcus theory extended to proton transfer reactions. 25a, 32 It was found that the kinetic data for a series of mutants under different buffer conditions can be fitted by Marcus theory with a very small intrinsic barrier of 1-2 kcal/mol and a large reorganization term (about 10 kcal/mol) for bringing the solvent and protein side chains into the right conformation for proton transfer. 25a The precise origin of this reorganization term is not completely clear, although it was suggested that it involves either orienting the bridging water molecules in the active site or a flip of the His64 side chain from an outward to inward orientation.…”
Section: Introductionmentioning
confidence: 99%
“…where the barrier heights can be read off from left to right in Figure 2 [45][46][47]. Because the transit time from one barrier to the next one a distance of a few angstroms away is less than a picosecond the proton arrives with some kinetic energy that has not been completely thermalized leading to a small reduction in the barrier heights.…”
Section: Discussionmentioning
confidence: 99%